Integration of BOLD-fMRI and DTI into radiation treatment planning for high-grade gliomas located near the primary motor cortexes and corticospinal tracts - Wang, Minglei (Radiat Oncol, 2015)
BACKGROUND: The main objective of this study was to evaluate the efficacy of integrating the blood oxygen level dependent functional magnetic resonance imaging (BOLD-fMRI) and diffusion tensor imaging (DTI) data into radiation treatment planning for high-grade gliomas located near the primary motor cortexes (PMCs) and corticospinal tracts (CSTs). METHODS: A total of 20 patients with high-grade gliomas adjacent to PMCs and CSTs between 2012 and 2014 were recruited. The bilateral PMCs and CSTs were located in the normal regions without any overlapping with target volume of the lesions. BOLD-fMRI, DTI and conventional MRI were performed on patients (Karnofsky performance score ≥ 70) before radical radiotherapy treatment. Four different imaging studies were conducted in each patient: a planning computed tomography (CT), an anatomical MRI, a DTI and a BOLD-fMRI. For each case, three treatment plans (3DCRT, IMRT and IMRT_PMC&CST) were developed by 3 different physicists using the Pinnacle planning system. RESULTS: Our study has shown that there was no significant difference between the 3DCRT and IMRT plans in terms of dose homogeneity, but IMRT displayed better planning target volume (PTV) dose conformity. In addition, we have found that the Dmax and Dmean to the ipsilateral and contralateral PMC and CST regions were considerably decreased in IMRT_PMC&CST group (p < 0.001). CONCLUSIONS: In conclusion, integration of BOLD-fMRI and DTI into radiation treatment planning is feasible and beneficial. With the assistance of the above-described techniques, the bilateral PMCs and CSTs adjacent to the target volume could be clearly marked as OARs and spared during treatment.